Web-based internship recruitment system with integration of instant notification service for university students / Muhammad Haznor Haqiff Hamam, Siti Zulaiha Ahmad and Jasmine Lim Seow Tiap - Hamam, Muhammad Haznor Haqiff; Ahmad, Siti Zulaiha; Lim, Jasmine Seow Tiap (UiTM Cawangan Perlis, 2025)
The critical role of internships in IT education is emphasized by rapid technological advancements, yet challenges such as limited platform availability and inefficient job posting processes persist. At UiTM Perlis, students face difficulties with manual document organization and finding internships, while organizations depend on coordinators for placements. This project introduces a web-based recruitment system integrating the Onyx Berry WhatsApp API for job notifications to address these issues. The system, which was created following the simplified System Development Life Cycle (SDLC) model, received a 90.8% satisfaction rate during user acceptance testing, which involved 30 students and 5 company staff. It significantly benefits students by streamlining internship applications, organizations by improving job posting efficiency, and coordinators by reducing administrative workload. Future improvements could include geo-spatial elements with Google Maps, direct communication features, comprehensive recruitment scheduling, and community-building, alongside user feedback mechanisms for continuous enhancement.